Economic and health impacts of China’s comprehensive health care system reform - Guangya Sun; Yaping Sun (Journal of Applied Economics)
We estimate the effects of the Comprehensive Medical Reform (CMR), a large-scale and comprehensive health care system reform in China, on medical burden and health status. Leveraging a time-varying difference-in-differences methodology and utilizing microdata from the Chinese Family Panel Study (CFPS), we demonstrate that exposure to the CMR leads to significant reduction in individuals’ out-of-pocket medical expenses and an improvement in their health status. Notably, there are no substantial changes in total medical expenses. Additionally, we find that the CMR enhances medical satisfaction and level, expands health insurance coverage, and increases residents’ propensity to select lower-grade hospitals. Lastly, we uncover that the economic and health effects vary among different groups of individuals.